2002
DOI: 10.1002/1521-3838(200205)21:1<23::aid-qsar23>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Fragmental Methods in the Design of New Compounds. Applications of The Advanced Algorithm Builder

Abstract: Fragmental methods (FMs) have great potential in many practical areas related to the design of new lead compounds. Advanced Algorithm Builder TM (AAB) is a new software system which employs FMs in (i) building QSPR, QSAR and SAR models, (ii) converting them to custom (in-house) algorithms and screening filters, and (iii) predicting physical properties and biological activities for new compounds. This review demonstrates how FMs and AAB can be used to substantiate our intuition, interpret observations, validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Japertas et al [262] reported a fragment-based method while a more rigorous method based on quantum mechanics calculations has been described by Gancia et al [263] The latter method was based on the premise that Abraham's H-bond scales could be related to parameters derivable from quantum-mechanical calculations such as atom self-polarizability and electrophilic superdelocalizability. These are, broadly speaking, parameters that include terms relating to the degree to which a given molecular orbital receives a contribution from an atomic orbital, and the energy of the orbital.…”
Section: Water and Hydrogen Bondsmentioning
confidence: 99%
“…Japertas et al [262] reported a fragment-based method while a more rigorous method based on quantum mechanics calculations has been described by Gancia et al [263] The latter method was based on the premise that Abraham's H-bond scales could be related to parameters derivable from quantum-mechanical calculations such as atom self-polarizability and electrophilic superdelocalizability. These are, broadly speaking, parameters that include terms relating to the degree to which a given molecular orbital receives a contribution from an atomic orbital, and the energy of the orbital.…”
Section: Water and Hydrogen Bondsmentioning
confidence: 99%
“…Molecule fragmentation and all subsequent statistical analysis were performed using Algorithm Builder 1.8 software [35,36], except SVM and Random Forest models which were developed using R 2.6.2 [37]. ROC curves were generated by a web-based calculator [38].…”
Section: Softwarementioning
confidence: 99%
“…It is believed that the biological activity is related to the lipophilicity, thus the 1-octanol/water partition coefficient [43][44][45][46][47][48][49][50] and molecular polar surface area (PSA) [51] of compound were calculated. The values of average log P equal to 1.31 (22) and PSA equal to 70.72 Å 2 suggest the concept that the compound can be transported via biological membranes to binding site.…”
Section: Structures and Bonds Propertiesmentioning
confidence: 99%